The Relationship between Religiosity and Resilience among Thesis Program Students at Sunan Ampel State Islamic University - Munawaroh; Moh Sholeh; Faizah Oktaviani (Al Qalam, 2025)
Students with low resilience in preparing a thesis are prone to stress, depression, and wanting to end their lives. This study aims to determine the relationship between religiosity and resilience in students enrolled in thesis programs. This study is a correlational quantitative study. The data collection tools used in this study were a resilience scale and a religiosity scale. The subjects in this study were 32 students selected through purposive sampling. Hypothesis testing in this study used simple linear regression analysis with the help of SPSS. The results of the study showed a significant relationship between religiosity and resilience in active students in the thesis program. In other words, the better the religiosity of students in the thesis program, the better their level of resilience, and conversely, the lower the religiosity of students in the thesis program, the lower their level of resilience.